Gene transcription profiling of astheno- and normo-zoospermic sperm subpopulations - Caballero-Campo, Pedro (Asian J Androl, 2020)
Spermatozoa contain a repertoire of RNAs considered to be potential functional fertility biomarkers. In this study, the gene expression of human sperm subpopulations with high (F1) and low (F2) motility from healthy normozoospermic (N) and asthenozoospermic (A) individuals was evaluated using RNA microarray followed by functional genomic analysis of differentially expressed genes. Results from A–F1 versus N–F1, A–F2 versus N–F2, N–F1 versus N–F2, and A–F1 versus A–F2 comparisons showed a considerably larger set of downregulated genes in tests versus controls. Gene ontology (GO) analysis of A–F1 versus N–F1 identified 507 overrepresented biological processes (BPs), several of which are associated with sperm physiology. In addition, gene set enrichment analysis of the same contrast showed 110 BPs, 36 cellular components, and 31 molecular functions, several of which are involved in sperm motility. A leading-edge analysis of selected GO terms resulted in several downregulated genes encoding to dyneins and kinesins, both related to sperm physiology. Furthermore, the predicted activation state of asthenozoospermia was increased, while fertility, cell movement of sperm, and gametogenesis were decreased. Interestingly, several downregulated genes characteristic of the canonical pathway protein ubiquitination were involved in asthenozoospermia activation. Conversely, GO analysis of A–F2 versus N–F2 did not identify overrepresented BPs, although the gene set enrichment analysis detected six enriched BPs, one cellular component, and two molecular functions. Overall, the results show differences in gene transcription between sperm subpopulations from asthenozoospermic and normozoospermic semen samples and allowed the identification of gene sets relevant to sperm physiology and reproduction.